Left and right atrial speckle tracking: Comparison of three methods of time reference gating. Issue 7 (20th June 2020) - Palmer, Cassady; Truong, Vien T.; Klas, Berthold; Wolking, Sarah; Ornella, Allison; Young, Michael; Ngo, Tam N. M.; Tretter, Justin T.; Nagueh, Sherif F.; Mazur, Wojciech
Abstract: Background: Atrial function has a close interdependence with ventricular function and plays a central role in maintaining optimal cardiac function. There are two well‐defined timing methods used to determine the start point. The aim of this prospective study was to objectively assess the influence of gating method selection on reported left and right strain values within the same group of healthy subjects. Methods: 101 volunteers (44 male, 57 female) had adequate tracking for analysis on TomTec Imaging Systems (Unterschleissheim, Germany). The median age was 41 years (range 19‐79 years, interquartile range 30‐52 years). Atrial strain by 2D‐speckle tracking echocardiography was evaluated using two commonly applied zero baseline time reference methods: R‐R gating and P‐P gating, in addition to volume gating (defining end‐systole at the atrial maximum and end‐diastole at the atrial minimum). Results: True atrial minimum occurred prior to the onset of the QRS in most healthy volunteers. There was a significant difference for LA and RA reservoir strain between volume gating and R‐R gating (mean difference, 4.63%; P  < .001 for LA; mean difference, 4.23%; P  < .001 for RA), as well as volume gating and P‐P gating (mean difference, 5.26%; P  < .001 for LA; mean difference, 6.24%; P  < .001 for RA). Noticeably, reservoir strain was comparable between R‐R gating and P‐P gating (mean difference, 0.58%, P  = .06) in LA, but not on RA (mean difference, 2.02%, P  < .001). Conclusions: There was variability in atrial strain values depending on the zero baseline time reference method used.